Tropical Deltas and Coastal Zones Food Production, Communities and Environment at the Land–Water Interface - Chu T, Hoanh (CABI, 2014)
Tropical megadeltas contain some of the most significant areas of urban, agricultural and industrial development in the world. These regions also possess ecosystems that are both critically important and highly endangered, and hold a rich collection of historical and cultural resources. The increasing pace of human development activities in tropical megadeltas has altered the functionality of these ecosystems drastically and produced escalating economic and sociocultural impacts that threaten critical food-producing areas. Tropical megadeltas have long been under stress from overexploitation and mismanagement, and now the looming spectre of sea-level rise associated with global warming presents a new and potentially far more dangerous threat to these regions. Delta 2007 held in Bang Sean, Thailand, in November 2007 brought together a diverse range of research scientists to examine the state of tropical megadeltas, with a particular focus on agriculture, fisheries, aquaculture and the environment. This book is a compendium of selected papers from the conference that can be broadly categorized as land and water management, fisheries and aquaculture and rice-based agriculture systems. Intensification of aquaculture and rice-based agriculture frequently produces negative effects that range from environmental degradation to social conflict; managing these impacts in a sustainable manner is imperative if we hope to protect the social and ecological foundations of tropical deltaic systems. New approaches to the intensification and diversification of rice-based production systems are presented in this book, which could impact positively on the livelihoods of millions who inhabit the deltaic areas of South, South-east and East Asia if implemented on a large scale. More importantly, these innovations could begin to reverse our current exploitive behaviour and ensure the preservation of critical ecosystems. A significant section of the compendium is devoted to the intensification of marine shrimp aquaculture production. Negative impacts associated with shrimp production are well recognized, and several innovative approaches to waste management are presented. Further critical questions are raised over the introduction of exotic shrimp species and the long-term impact this could have on native species, which suggests a cautionary approach to future development.